Neverseen - Messenger, Shannon (Messenger, Shannon. Keeper of the lost cities, 2016)
Sophie is on the run with her best friends. They plan to join the Black Swan, despite their doubts about the organization. But their enemies aren't done with them yet, and they must be careful who they trust or they may not survive.